cGAS-STING targeting offers therapy choice in lung diseases - Yu Wang; Xuan Zhang; Weixue Wang; Yi Zhang; Joshua S. Fleishman; Hongquan Wang (Biology Direct, 2025)
Abstract Cyclic GMP/AMP (cGAMP) synthase (cGAS), along with the endoplasmic reticulum (ER)-associated stimulator of interferon genes (STING), are crucial elements of the type 1 interferon response. cGAS senses microbial DNA and self-DNA, labeling cGAS-STING as a crucial mechanism in autoimmunity, sterile inflammatory responses, and cellular senescence. However, chronic and aberrant activation of the cGAS-STING axis results in inflammatory and autoimmune diseases. cGAS-STING has emerged as a vital mechanism driving inflammation-related diseases, including lung diseases. Insights into the biology of the cGAS-STING pathway have enabled the discovery of small-molecule agents which have the potential to inhibit the cGAS-STING axis in lung diseases. In this review, we first outline the principal components of the cGAS-STING signaling cascade. Then, we discuss recent research that highlights general mechanisms by which cGAS-STING contributes to lung diseases. Then, we focus on summarizing a list of bioactive small-molecule compounds which inhibit the cGAS-STING pathway, reviewing their potential mechanisms.These review highlights a novel groundbreaking therapeutic possibilities through targeting cGAS-STING in lung diseases.